Ketorolac Administered in the Recovery Room for Acute Pain Management Does Not Affect Healing Rates of Femoral and Tibial Fractures. Issue 9 (September 2016) - Donohue, David; Sanders, Drew; Serrano-Riera, Rafa; Jordan, Charles; Gaskins, Roger; Sanders, Roy; Sagi, H. Claude
Abstract : Objectives: To determine whether ketorolac administered in the immediate perioperative period affects the rate of nonunion in femoral and tibial shaft fractures. Design: Retrospective comparative study. Setting: Single Institution, Academic Level 1 Trauma Center. Patients: Three hundred and thirteen skeletally mature patients with 137 femoral shaft (OTA 32) and 191 tibial shaft (OTA 42) fractures treated with intramedullary rod fixation. Intervention: Eighty patients with 33 femoral shaft and 52 tibial shaft fractures were administered ketorolac within the first 24 hours after surgery (group 1—study group). Two-hundred thirty-three patients with 104 femoral shaft and 139 tibial shaft fractures were not (group 2—control group). Main Outcome Measurements: Rate of reoperation for repair of a nonunion and time to union. Results: Average time to union of the femur was 147 days for group 1 and 159 days for group 2 ( P = 0.57). Average time to union of the tibia was 175 days for group 1 and 175 days for group 2 ( P = 0.57). There were 3 femoral nonunions (9%) in group 1 and eleven femoral nonunions (11.6%) in group 2 ( P = 1.00). There were 3 tibial nonunions (5.8%) in group 1 and 17 tibial nonunions (12.2%) in group 2 ( P = 0.29). The average dose of ketorolac for patients who healed their fracture was 85 mg, whereas it was 50 mg for those who did not ( P = 0.27). All patients with a nonunion in the study group were current smokers. Conclusions: Ketorolac administered in the first 24 hours after fracture repair for acute pain management does not seem to have a negative impact on time to healing or incidence of nonunion for femoral or tibial shaft fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.